High-pressure phase behavior of poly(D,L-lactide) in chlorodifluoromethane, difluoromethane, trifluoromethane, and 1,1,1,2-tetrafluoroethane - Kuk, YM; Lee, BC; Lee, YW; Lim, JS (AMER CHEMICAL SOC, 2002)
Phase behavior data at temperatures from 303.15 K to 373.15 K and at pressures from 3 MPa to 85 MPa are presented for poly(D,L-lactide) in chlorodifluoromethane, difluoromethane, trifluoromethane, and 1,1,1,2-tetrafluoroethane. The cloud point pressures were measured using a high-pressure equilibrium apparatus equipped with a variable-volume view cell, and were investigated as functions of temperature, polymer concentration, and polymer molecular weight. Chlorodifluoromethane was the solvent with the highest solvent power, while trifluoromethane was the solvent with the lowest solvent power. The solvent power of hydrofluorocarbon solvents of dissolving the poly(D,L-lactide) increased in the order trifluoromethane, difluoromethane, and 1,1,1,2-tetrafluoroethane in proportion to their dipole moments.
Keywords: CARBON-DIOXIDE; SUPERCRITICAL CHLORODIFLUOROMETHANE; PARTICLES; MIXTURES